The Role Of Interpretive Signages In Enhancing Conservation Knowledge, Awareness And Behavior Among Visitors At The Penang National Park, Malaysia - Ismail, Mohd Hafizal (2008)

(untitled)
Interpretation is an approach of communication used in most national parks and recreation areas to reveal information, create awareness and overcome park problems such as littering and vandalism. An experimental study was conducted to determine the role of developed interpretive signages in conservation knowledge, awareness and behavior among visitors at Penang National Park (PNP). Interpretive signage with three different theme and storyline were designed using Tilden’s interpretation principles and were placed along PNP’s existing trails as treatment. The questionnaire survey was conducted before and after the visitors entered the park through Pasir Pandak entrance. The questionnaires were divided into three main sections and designed based on human basic psychological theory (belief, attitude and behavioral) to measure visitors perception towards natural environment, emotional effect and human rights. Similar set of questionnaire was used for before and after survey to observe differences in terms of respondents’ agreement. Respondents were divided into two groups, which were treatment and control groups. Treatment group was the target group to observe impact on effectiveness of interpretive signage towards their conservation awareness and attitude. Control group was the group who did not received any treatment during the study. About 266 pairs of questionnaires were collected from both groups which consisted of 228 pairs of the treatment group and 38 pairs of control groups. Results showed that most of both respondents were between 18 to 28 years old, students in tertiary education with monthly income of less than RM500 per month. Majority of these respondents came to PNP to gather some valuable experience and for enjoyment with friends. Overall, each sections of questionnaire showed significant differences and typically the impact of developed interpretive signage on visitors’ conservation awareness was highly influenced by their emotions. Results indicated that the respondents became more aware after they received the treatment. The impact of developed interpretive signages showed that they would take several actions as their new belief/perception towards natural resources such as giving advices to anyone or visitor who dropped litter in PNP’s natural area and willing to pick up any litter which they found along the trails. Impact on respondents’ knowledge can be observed when they realize that large numbers of visitors in a period of time would impact the resource. Initially, findings from this study proved that the impact on interpretive signages had essentially enhanced conservation awareness among the visitors and can be useful as a linkage for visitors to share their awareness and appreciation towards natural resources